CONTEMPORARY CRITIC CULTURE BETWEEN HERITAGE AND WESTERN THEORIES ANALYTICAL CRITICAL STUDY - Suliman, Essam Muhammed (Journal of Duhok University, 2018)
The present study attempts to uncover culture, it’s important and its status and excellence in the critic process that the contemporary critic has to acquire through critic and analysis. The relationship between the critic and his culture is one of the most prominent issues, issues and problems that affect in one way or another the authenticity of the intellectual critic and his strong conclusions, as well as finding the correct approach to building knowledge and independence in the view and away from the tradition and the original work of the monetary curricula after knowledge of its origins and cultural referential and philosophical or cognitive backgrounds. But what is happening in the critical cultural scene in our time are two important and dangerous things: the first is the weakness of contact with the cultural heritage, and the second is the rush to adopt this theory or the Western theories and to understand literary production in light of these theories. Both cases have unsafe and incorrect consequences.The research plan required dividing it into an introduction, a preface, three studies, and a conclusion, in which we presented the most important conclusions we reached. As for the introduction, we follow the concept of culture and what is the literary critic, but the preface we devoted to the terms of the good critic, the first subject and the position of critics old and modern ones and their impact in enriching literary criticism. As for the second topic, we talked about the position of contemporary critic on the heritage and its relevance to it and the impact of this link on literary criticism and then how to treat the weakness between the critic and heritage by reading the heritage in a new and deep way away from the prejudices.As for the second topic, we talked about the position of the contemporary critic on the heritage and its relevance to it and the impact of this link on literary criticism and then how to treat the weakness between the critic and heritage by reading the heritage reading new deep away from the prejudices and sorting out the pros of the negatives that have been suspended in this heritage. As for the third topic, we examined the position of the contemporary critic of the theories and methods of the literary criticism of the expatriate and not to rush to adopt it without knowledge of its cognitive or philosophical backgrounds because each theory emerged in the West was the result of long and inveterate philosophical thought. We have followed the critical analytical descriptive approach